CORAK PEMAHAMAN KARYAWAN KEMENTERIAN AGAMA KABUPATEN REJANG LEBONG TERHADAP KONSEP TAKDIR DAN KOHERENSINYA DENGAN ETOS KERJA (STUDI TEOLOGIS PEMAHAMAN TENTANG TAKDIR DAN ETOS KERJA) - Ombi Romli (Sekolah Pasca Sarjana IAIN Bengkulu, 2016)
Abstract: The purpose of this study is to know about the style of understanding the concept of destiny employees of the Ministry of Religious Rejang Lebong. The work ethic of employees Ministry of Religious Rejang Lebong and how coherence between the understanding of destiny with the work ethic. Research conducted qualitative, with a phenomenological approach. Who became an informant as a data source is partially employee Rejang Lebong Religious Affairs totaling 25 people, consisting of the organization’s leaders, the heads of sections., Organizer and supervisor of the Islamic religion and the staff all of whom are Muslims. Then the research data were analyzed using analytical techniques deskriftik. In this study, the authors wanted to know and to describe, the following matters: First, the style of understanding the concept of destiny employees of the Ministry of Religious Rejang Lebong, author klsifikasikan to tigaa jabariah pattern that is moderate, that gives meaning to the concept of destiny will be the synergy between the absolute freedom of God with the power of human endeavor. In addition there are patterned qodariah, who interpret memaberikan broadest freedom to power and the power of man, and the last, patterned extreme jabariah, who interpret destiny is the prerogative of God, men did not take part in it, like a puppet-driven human puppeteer. Second, the Ministry of Religious Affairs Employees Work Ethic Rejang Lebong. The result shows that in general, his work ethic were high. With the following indicators: a). Employee attitudes toward work:1.Fleksibilitas while working 2. Adjustment of work b). Feelings of an employee: 1. Control 2. senag bekerja. c job). The willingness of the employees to do the job: 1. Compliance work, 2. Willingness to complete the work, d). employees currently work: 1. The seriousness of the work The third of the coherence between the understanding of the concept of destiny with the work ethic. From the data I have found the results, that there is a significant relationship between the understanding of religious ministry employees destiny Rejang Lebong with his work ethic. Broadly speaking, that employees who patterned jabariah moderate ideology and Qodariyah work ethic tends to be high, employees were shades of understanding destiny jabariah extreme work ethic tends to be low.